Increasing Citizen's Motivation For Education Awareness, Economics And Gutong Royong In Building Better Villages - Arnita Dewi Wahyu (Journal of Community Service For Indonesian Society, 2023)
This research uses qualitative research. Which is where this qualitative research is descriptive using qualitative data analysis so that it becomes an easy-to-understand data exposure. In this KKN activity in 2022, PGSD UMSU carried out KKN activities still independently, even though the pandemic had reduced and all communities in each region had carried out many vaccination activities to prevent the transmission of COVID-19, but the COVID-19 Virus is still around us, Therefore, UMSU students are encouraged to carry out community service activities in their respective areas of residence in order to avoid the development of the COVID-19 virus. With the latest situation after more than three years of limited activities, now it has started to return to normal as usual and has started to carry out various kinds of activities such as face-to-face schools, tourist attractions and shopping centers have resumed operations, and various other activities. However, the level of public awareness in Denai Lama Village is low on the cleanliness and goodness of the environment in which they live. Therefore, UMSU KKN students came to carry out Independent Community Service activities in the Denai Lama Village environment with the aim of sharing the knowledge they got while in college, as well as helping the community's motivation to increase the value of community self-awareness in Denai Lama Village towards the goodness of their living environment. However, the level of public awareness in Denai Lama Village is low on the cleanliness and goodness of the environment in which they live. Therefore, UMSU KKN students came to carry out Independent Community Service activities in the Denai Lama Village environment with the aim of sharing the knowledge they got while in college, as well as helping the community's motivation to increase the value of community self-awareness in Denai Lama Village towards the goodness of their living environment. However, the level of public awareness in Denai Lama Village is low on the cleanliness and goodness of the environment in which they live. Therefore, UMSU KKN students came to carry out Independent Community Service activities in the Denai Lama Village environment with the aim of sharing the knowledge they got while in college, as well as helping the community's motivation to increase the value of community self-awareness in Denai Lama Village towards the goodness of their living environment.